Nutritional therapy in hospital care of in-patients with Covid-19: evidence, consensus and practice guidelines - Koester WEBER, Thabata [UNESP]; Leandro-Merhi, Vania Aparecida; Bernasconi, Isabela; Bang, Shalakha V [UNESP] (Universitat Autonoma de Barcelona, 2020)
Objective The objective of this work was to review papers that deal with nutritional therapy of inpatients with Covid-19 from the beginning of the pandemic. The survey covered the period until the month of September 2020. Methods This is a review of the indexed literature (Scopus, Pubmed and Lilacs), including area consensus. Results The review showed that the initial recommendations were based on generic assumptions and, as specific knowledge was being produced, the recommendations became more targeted.
Keywords: Coronavirus infection; Nutrition therapy; Nutritional status